Flexible high‐resolution full‐color top‐emitting active‐matrix organic light‐emitting diode display. Issue 10 (21st November 2013) - Chida, Akihiro; Aoyama, Tomoya; Eguchi, Shingo; Inoue, Tatsunori; Senda, Naoyuki; Sakuishi, Tatsuya; Ikeda, Hisao; Shitagaki, Satoko; Ohsawa, Nobuharu; Inoue, Hideko; Suzuki, Kunihiko; Seo, Hiromi; et al.
Abstract We developed a high‐performance 3.4‐in. flexible active‐matrix organic light‐emitting diode (AMOLED) display with remarkably high resolution using an oxide semiconductor in a backplane, by applying our transfer technology that utilizes metal separation layers. Using this panel, we also fabricated a prototype of a side‐roll display for mobile uses. In these AMOLED displays, a white OLED combined with a color filter was used in order to achieve remarkably high resolution. For the white OLED, a tandem structure in which a phosphorescent emission unit and a fluorescent emission unit are serially connected with an intermediate layer sandwiched between the emission units was employed. Furthermore, revolutionary technologies that enable a reduction in power consumption in both the phosphorescent and fluorescent emission units were introduced to the white tandem OLED.